Revisiting the orality-literacy relationship and its implications for English language teaching in Bangladesh - Ali, Md Maksud (IIUC Studies, 2017)
This paper focuses on different concepts of literacy and their implications for TESOL (Teaching English to Speakers of Other Languages). Taking a critical perspective, the study examines the traditional concept of literacy and illuminates how a narrow approach to literacy may lead to a conflict between national policy text and the actual pedagogic practices. Therefore, the author advocates for situating contemporary TESOL pedagogy within a broader concept. In addition, the study examines how literacy is embedded with orality, and whether the link between them has any implications for English language education in Bangladesh. It is argued here that since different cultures and societies do not adhere to a single set of literacy practices, an awareness of learners’ and other stakeholders’ socio-cultural concepts of literacy in a society is essential for TESOL practitioners in order for their materials and methods to be socio-culturally responsive. The study has implications for policy makers, materials writers and TESOL practitioners. IIUC Studies Vol.14(2) December 2017: 99-110